Effects of morphological processes in the nativisation of loanwords in Anufo: A linguistic analysis - Tasson, Solomon Kofi (Research Journal in Advanced Humanities, 2022)
The study was to determine the morphological processes that affect loanwords in Anufo. The research approach used was qualitative and the design is case study. The data collection strategies used for the study were interview, observation, and documents. The theoretical framework used for the study is Basic Linguistic Theory (Dixon 2010). The study established that Anufo has historically and socially heavily borrowed words from the three main languages, English, Likpakpaln and Akan, to fill lexical gaps. Apart from nouns, the main types of words that are borrowed into Anufo are adjectives, verbs, adverbs, and conjunctions. Phonologically, it came out that Anufo has twenty-seven consonant sounds while English has twenty-four. This study is distinct from others because it looks at loanwords from three different languages: English, Likpakpaln and Twi. Borrowing in Anufo is distinct from other Ghanaian languages such as Likpakpaln. This is because Likpakpaln has closed syllable types like that of English language. Anufo syllables are of the open type therefore, when the borrowed word has a closed syllable, it must be repaired to be nativized. The study contributes greatly to the literature of loanwords because it has been realized that no vowel apart from /a/ can occur at word initial position of Anufo. So, when a borrowed word into Anufo has a vowel other than /a/ at its initial position needs to go through some repair strategies for such a word to be nativised. A semantic and a comparative study of loanwords are recommended to find out differences and similarities of loanword adaptation strategies in the Ghanaian languages.